Mid-femur geometry and biomechanical properties in 15- to 18-yr-old female athletes - Duncan, C. S.; Blimkie, C. J.; Kemp, A.; Higgs, W.; Cowell, C. T.; Woodhead, H.; Briody, J. N.; Howman-Giles, R. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: Right-leg mid-femur geometry and biomechanical indices of bone strength were compared among elite cyclists (CYC), runners (RUN), swimmers (SWIM), triathletes (TRI), and controls (C)-10 subjects per group. METHODS: Bone cross-sectional areas (CSA), volumes (Vol), and cross-sectional moments of inertia (CSMI) were assessed by magnetic resonance imaging (MRI), and cortical volumetric bone density (volBMD) was determined as the quotient of DXA-derived bone mineral content (BMC) and MRI-derived cortical bone volume. Bone strength index (BSI) was calculated as the product of cortical volBMD and CSMI. RESULTS: RUN had higher (P < 0.05) size- (femur length and body mass) adjusted (ANCOVA) cortical CSA than C, SWIM, and CYC; and higher size, age, and years of sport-specific training- (YST) adjusted cortical CSA than SWIM and CYC. TRI had higher (P < 0.05) size-adjusted CSA than SWIM. SWIM and CYC had significantly larger (P < 0.05) size-adjusted medullary cavity CSA than RUN and TRI, and the difference between CYC and RUN persisted after additional adjustment for age and YST. RUN had significantly (P < 0.05) greater size-adjusted CSMI and BSI than C, SWIM, and CYC; and higher size, age, and YST-adjusted CSMI and BSI than SWIM and CYC. Mid-femur areal bone mineral density (BMD) was significantly (P < 0.05) higher for RUN compared with CYC only, but there were no other differences among groups for BMC, bone volumes, or volumetric total or cortical BMD. CONCLUSIONS: Running, a weight-bearing exercise, is associated with more favorable geometric and biomechanical characteristics in relation to bone strength, compared with the weight supported activities of swimming and cycling. Differences may reflect skeletal adaptations to the specific mechanical-loading patterns inherent in these sports.